Internalisasi Pendidikan Moderasi Beragama dalam Sistem Pendidikan Dayah Tradisional di Kota Langsa. (Studi Kasus di Dayah Tradisonal Raudhatun Najah Kota Langsa) - Muhaini Muhaini (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This paper describes how traditional dayah internalizes moderate value. Differences of religious understandings, thoughts, sects and its practices sometimes very transcendental. These diversities bring disaster, victims, and lives on behalf of religion. In the last decade, the Indonesian government through the ministry of religion affairs launched the slogan of religious moderation as a peaceful step in a highly hydrogenated life. The most powerful way to prevent violence, radicalism, inclusivism and fight is by moderate Islamic education way. This study uses a qualitative approach. Data collection techniques using interview (in dept interview), observations in learning process and campus life of students in dayah, study documentation, researcher analyze the texts being taught. The data were analyzed using the Miles and Hubberman technique. The conclusion of this study shows traditional dayah Islamic education system have several indicators and efforts in learning tutorial on process. Doctrines and transferring values of religious moderation also practiced in the daily studentsâ€™ life.Â